Artificial Intelligent Virtual Assistant for Plastic Surgery Patient's Frequently Asked Questions: A Pilot Study. Issue 4 (April 2020) - Boczar, Daniel; Sisti, Andrea; Oliver, Jeremie D.; Helmi, Haytham; Restrepo, David J.; Huayllani, Maria T.; Spaulding, Aaron C.; Carter, Rickey; Rinker, Brian D.; Forte, Antonio Jorge
Abstract : Background: Artificial Intelligent Virtual Assistants (AIVA) is a segment of artificial intelligence that is rapidly developing. However, its utilization to address patients' frequently asked questions remains unexplored. Methods: We developed an AIVA to answer questions related to 10 frequent topics asked by plastic surgery patients in our institution. Between July 27, 2018, and August 10 of 2018, we recruited subjects with administrative positions at our health care institution to chat with the virtual assistant. They asked, with their own words, 1 question for each topic and filled out a satisfaction questionnaire. Postsurvey analysis of questions and answers allowed assessment of the virtual assistant's accuracy. Results: Thirty participants completed the survey. The majority was female (70%), and the mean age was 27.76 years (SD, 8.68 [19–51] years). The overall accuracy of the plastic surgery AIVA was 92.3% (277/294 questions), and participants considered the answer correct in 83.3% of the time (250/294 answers). Most of the participants considered the AIVA easy to use, answered adequately, and could be helpful for patients. However, when asked if this technology could replace a human assistant, they stayed neutral.